First-Principle Insight Into the Effects of Oxygen Vacancies on the Electronic, Photocatalytic, and Optical Properties of Monoclinic BiVO4(001) - Gu, Xiaosong; Luo, Yujie; Li, Qi; Wang, Rui; Fu, Shiqi; Lv, Xiulong; He, Qian; Zhang, Ying; Yan, Qiutong; Xu, Xuan; Ji, Fangying; Qiu, Yan (Frontiers in Chemistry, 2020)
In this paper, ﬁrst-principle calculations were performed to investigate the effects of oxygen (O) vacancies (Ovac) on the crystal structure, electronic distribution, adsorption energies of O2 and H2O and the density of states (DOS) of monoclinic bismuth vanadate (m-BiVO4). Ovac were stable when incorporated into m-BiVO4(001) and increased the adsorption energy of O2. Ovac changed the V3d orbitals of m-BiVO4(001) by adding a new band gap level, causing the redundant electrons of V atoms to become carriers and promoting the separation efficiency of electrons and holes. To verify the ﬁrst-principle calculations, m-BiVO4 with different Ovac levels was prepared via hydrothermal synthesis. X-ray diﬀraction (XRD) patterns confirmed the existence of the (001) crystal surface of m-BiVO4. In addition, X-ray photoelectron spectroscopy (XPS) and electron spin resonance (ESR) spectroscopy of m-BiVO4 confirmed the presence of Ovac and demonstrated that, as the Ovac level increased, the number of superoxide radicals (·) and hydroxyl radicals (·OH) produced increased. In addition, m-BiVO4 with a higher Ovac level possessed superior photocatalytic properties to and degraded rhodamine B (RhB) dye nearly two-fold faster than m-BiVO4 with a lower Ovac level. Finally, the removal rate of RhB increased from 23% to 44%. All experimental results were in good agreement with the ﬁrst-principle calculated results.